Prenatal diagnosis of low-level mosaic trisomy 17 with maternal uniparental disomy 17 by amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Shin-Yu Lin; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Wayseen Wang (Elsevier, 2020)
Objective: We present prenatal diagnosis low-level mosaic trisomy 17 with maternal uniparental disomy (UPD) 17 at amniocentesis in a pregnancy with a favorable outcome. Materials and methods: A 40-year-old, primigravid woman underwent amniocentesis at 18 weeks of gestation because of advanced maternal age. This pregnancy was conceived by in vitro fertilization and embryo transfer. Amniocentesis revealed a karyotype of 47,XX,+17 [13]/ 46, XX [23]. Repeat amniocentesis was performed at 21 weeks of gestation. Conventional cytogenetic analysis was applied on cultured amniocytes, parental bloods and cord blood. Simultaneous molecular genetic analysis such as interphase fluorescence in situ hybridization (FISH), array comparative genomic hybridization (aCGH) and quantitative fluorescent polymerase chain reaction (QF-PCR) assays were applied on uncultured amniocytes. Interphase FISH was applied on postnatal buccal cells. Results: Repeat amniocentesis revealed a karyotype of 47,XX,+17[6]/46,XX[28]. Genetic analyses on uncultured amniocytes showed the results of mosaic trisomy 17 (12/101 cells = 11.9%) in FISH analysis, no genomic imbalance in aCGH analysis and maternal UPD 17 in QF-PCR assays. The parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. The parents decided to continue the pregnancy, and a 1449-g, phenotypically normal female baby was delivered prematurely at 31 weeks of gestation. The cord blood had a karyotype of 46,XX. She had a normal psychomotor development at age 22 months at follow-up. Interphase FISH analysis on buccal cells showed trisomy 17 signals in 1/66 cells (1.5%). Conclusions: Low-level mosaicism for trisomy 17 associated with maternal UPD 17 detected by amniocentesis without ultrasound abnormality can be associated with a favorable outcome. Molecular genetic analysis of uncultured amniocytes at repeat amniocentesis is useful for confirmation and genetic counseling under such as circumstance. Keywords: amniocentesis, Maternal uniparental disomy 17, Mosaic trisomy 17, Prenatal diagnosis